Implementation of Emotional Spiritual Quotient in Character Building of Students at MTs Mursyidul Awwam Cenrana, Bone Regency - Syarifuddin, Samsinar S; Husna, Asmaul; Muh. Bachtiar Aziz; Suriani Nur (DIDAKTIKA, 2025)
This study discusses the implementation of Emotional Spiritual Quotient (ESQ) in shaping students' character at MTs Mursyidul Awwam Cenrana, Bone Regency. The purpose of this study is to analyze teachers’ strategies in applying ESQ to students, identify its implications for character development, and evaluate the impact of ESQ implementation. This research uses a qualitative descriptive method with pedagogical, psychological, and sociological approaches. Data collection techniques include observation, interviews, and documentation, using observation guidelines, interview guides, and document analysis as research instruments. The data analysis process involves data reduction, data presentation, and drawing conclusions. The findings indicate that the implementation of ESQ effectively contributes to the emotional and spiritual development of students’ character. Habit-forming activities serve as the foundation for character building. The impact of ESQ implementation at MTs Mursyidul Awwam Cenrana is evident in significant improvements in students' sense of responsibility, discipline, and religious attitudes